PENATAAN KORIDOR KAWASAN SEKUMPUL MARTAPURA SEBAGAI WISATA RELIGI - Hadi, Meidina Kartika; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Sekumpul, Martapura is acknowledged as a religious tourism destination by Banjar District’s Department of Tourism. Its number of visitors increase rapidly each year, crowding the streets especially in Martapura and Banjarbaru. Yearly, monthly, and even weekly events attract a lot of pilgrims, which boost the economic sector of the local community. This location, which was popularized by K.H. Abdul Ghani (also known as Guru Sekumpul) has now been filled with many activities. Unfortunately, the physical condition of Sekumpul can no longer accommodate the locals nor the pilgrims. The problem of traffic jams, discomfort and unsafety of pedestrians, and even the dryness of the area must be given solutions so that existing facilities will not go to waste. To solve these problems, the “walkable place” concept is applied, which uses the “sense of place” method with its 3 aspects (form, image, and activities). The walkable place concept is considered suitable and applicable for Rearrangement of Sekumpul Corridor, Martapura, solving problems of the physical conditions by road widening while still considering the existing conditions, adding amenities, creating positive spaces, optimizing the potential of the religious and commercial sectors, and also strengthening Sekmpul’s sense of place. The identity and character already formed in Sekumpul cannot be ignored and changed, therefore this design conserves while also developing for the good of the users.